Deep breathing as a mindfulness practice in year 10 science. (2nd January 2018) - King, Donna; Henderson, Senka; Sandhu, Maryam
ABSTRACT: Abdominal deep breathing (DB) has been used in conjunction with paying attention on purpose to the present moment as a mindfulness tool to help students develop skills for managing emotions. While studies are emerging that investigate outcomes of mindfulness practices with adolescents, how to implement such practices, and students' reactions to them, requires further research. This study examines a DB intervention in a year 10 science class where the teacher implemented DB exercises in each science lesson. One main outcome reported in this study is that the time to adapt to the DB exercises and experience its effectiveness varied for individual students. Gleaned from our presence in the classroom and speaking with the teacher and students, we suggest nine recommendations for implementing DB exercises in Australian middle years classrooms.